Organization and Evolutionary Trajectory of the Mating Type (MAT) Locus in Dermatophyte and Dimorphic Fungal Pathogens - Li, Wenjun (American Society for Microbiology (ASM), 2010)
Sexual reproduction in fungi is governed by a specialized genomic region, the mating type (MAT) locus, whose gene identity, organization, and complexity are diverse. We identified the MAT locus of five dermatophyte fungal pathogens (Microsporum gypseum, Microsporum canis, Trichophyton equinum, Trichophyton rubrum, and Trichophyton tonsurans) and a dimorphic fungus, Paracoccidioides brasiliensis, and performed phylogenetic analyses. The identified MAT locus idiomorphs of M. gypseum control cell type identity in mating assays, and recombinant progeny were produced. Virulence tests in Galleria mellonella larvae suggest the two mating types of M. gypseum may have equivalent virulence. Synteny analysis revealed common features of the MAT locus shared among these five dermatophytes: namely, a small size (∼3 kb) and a novel gene arrangement. The SLA2, COX13, and APN2 genes, which flank the MAT locus in other Ascomycota are instead linked on one side of the dermatophyte MAT locus. In addition, the transcriptional orientations of the APN2 and COX13 genes are reversed compared to the dimorphic fungi Histoplasma capsulatum, Coccidioides immitis, and Coccidioides posadasii. A putative transposable element, pogo, was found to have inserted in the MAT1-2 idiomorph of one P. brasiliensis strain but not others. In conclusion, the evolution of the MAT locus of the dermatophytes and dimorphic fungi from the last common ancestor has been punctuated by both gene acquisition and expansion, and asymmetric gene loss. These studies further support a foundation to develop molecular and genetic tools for dermatophyte and dimorphic human fungal pathogens.